Microclimate for cultural heritage - Camuffo, Dario (Developments in atmospheric science, 1998)
This is a useful microphysics handbook for conservators and specialists in physics, chemistry, architecture, engineering, geology and biology dealing with the environment and works of art. A rigourous treatment and a background familiarity with the underlying physics behind mathematics are covered, giving a detailed description and interpretation of the main microphysical phenomena, removing unsound popular beliefs. The basis are given for non-destructive diagnostics to evaluate causes of damage determined by atmoshpheric factors, as well as negative consequences of the unsound use of technology and mass tourism. To this aim, suggestions are given on the fundamental principles in designing heating, air conditioning, lighting and in reducing the deposition of pollutants on works of art. Theory and experience are coupled to describe the complex condensation mechanisms and the fundamental role played by water in the stone deterioration and the formation of crusts on monuments. Urban meteorology, air-surface interactions, atmospheric stability, dispersion and deposition of airborne pollutants are also key topics of this book, for which the main aim has been to make comprehensible to a wider audience a matter that is only familiar to a few specialists. This book combines a theoretical background with many years of accurate laboratory research, field surveys and practice. The first part, devoted to applied theory, is a concise treatise on microphysics, which includes a survey on the basic ideas which are necessary for environmental diagnostic and conservation. The second part of the book focuses on the practical utilisation and shows in detail how field surveys should be performed, with many suggestions and examples and the indication of some common errors that should be avoided.